The Construction of a Learner-centered Evaluation Framework Model for Community Education Quality in China (Journal of Global Humanities and Social Sciences, 2025)
The quality evaluation of community education needs an appropriate framework and toolkit to improve and monitor the quality in the field of community education． On the basis of clarifying the relevant theories of the quality of community education, this paper proposes a reference model with learner-centered perspective and a framework implementation of the proposed model, hoping to improve the quality evaluation drastically in the near future.